A divisão do trabalho no ambiente de aprendizagem de Modelagem Matemática segundo a Educação Matemática Crítica - Ilaine da Silva Campos (2018)
The research focus was to understand how the Division of Labor among students is constituted, organized in group, in the development of a Mathematical Modelling activity proposed according to Critical Mathematical Education theoretical guidelines. Over the investigation, I had as a direction to discuss how, from the Division of Labor, students' actions get close and far to what is expected when proposing such an activity in the classroom. The research was carried out in a 3rd year class of the High School Integrated Environment Technical Course, at the Federal Institute of Minas Gerais (IFMG), Governador Valadares Campus, from which a group was chosen for the analysis. For investigation development, I implemented along with the class teacher, a Modelling learning environment, seeking to follow Critical Mathematics Education theoretical guidelines. The research is of qualitative nature and data were produced through participant observation and interviews with the student group and the teacher. The concept of the Division of Labor comes from the Activity Theory, which has its origin in the Cultural-Historical School of Soviet Psychology. Students actions analysis based on this concept focused on the tasks with which the students were involved and how power relations were established and how was constituted the status among the group members in the Modelling activity development. With the analysis, it was evidenced that, at several moments, there were possibilities, from students actions, to break with school (Mathematics) Education tradition and other possibilities that strengthen this tradition. It was possible to conclude that Modelling learning proposed according to the theoretical approach of Critical Mathematics Education fails to favor significant disruptions with school (Mathematics) Education tradition, but small disruptions are possible that cause some perturbations in what seems strongly solidified by this tradition. The analysis of the Division of Labor enabled me to understand how the nature of the tasks favored or not the performance of certain group members in the development of the Modelling project, to understand how it was given from the relations of power established in the course of the Modelling activity, as the relations between the subjects, from the tasks, favored the status they occupied in the development of the Modelling activity or how the prevailing status in the group prevailed among the students as part of a class. The discussion developed in the present thesis contributes to the field of Modelling in Mathematical Education by putting in debate the power relations that constitute the Division of Labor in an Activity of a collective nature, explaining new elements that imply in the insertion of Modelling in the classroom